Wearable Devices for Assessment of Tremor - Vescio, Basilio; Quattrone, Andrea; Nisticò, Rita; Crasà, Marianna; Quattrone, Aldo (Frontiers in Neurology, 2021)
Tremor is an impairing symptom associated with several neurological diseases. Some of such diseases are neurodegenerative and tremor characterization may be of help in differential diagnosis. To date, electromyography (EMG) is the gold standard for the analysis and diagnosis of tremors. In the last decade, however, several studies have been conducted for the validation of different techniques and new, non-invasive, portable, or even wearable devices have been recently proposed as complementary tools to EMG for a better characterization of tremors. Such devices have proven to be useful for monitoring the efficacy of therapies, or even aiding in differential diagnosis. The aim of this review is to present systematically such new solutions, trying to highlight their potentialities and limitations, with a hint to future developments.